2000
DOI: 10.1034/j.1600-0501.2000.011003217.x
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus augmentation using xenogenic bone substitute material Bio‐Oss® in combination with venous blood

Abstract: The aim of the present study was to evaluate bone formation following maxillary sinus augmentation using bovine bone substitute material Bio-Oss in combination with venous blood by means of histologic and histomorphometric examination of human biopsies. This involved a total of 15 sinus floor elevation procedures being carried out on 11 patients (average age of 49.6 years) according to the technique described by Tatum (1986). The subantral sinus cavity was augmented using bovine apatite combined with venous bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
255
3
13

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(294 citation statements)
references
References 31 publications
23
255
3
13
Order By: Relevance
“…While some bone substitutes undergo almost immediate biodegradation and resorption, others can be detected on the implant site for several years [1,18]. Moreover, some materials are reported to have better osteointegration with host bone [19].…”
Section: British Biomedical Bulletin Issn 2347-5447mentioning
confidence: 99%
See 2 more Smart Citations
“…While some bone substitutes undergo almost immediate biodegradation and resorption, others can be detected on the implant site for several years [1,18]. Moreover, some materials are reported to have better osteointegration with host bone [19].…”
Section: British Biomedical Bulletin Issn 2347-5447mentioning
confidence: 99%
“…Although allografts, xenegrafts as well as synthetic regenerative materials have shown satisfactory results in clinical applications [17], the resorption rate of regenerative material, the quality of bone formed as well as the rate of bone formation are determined by the type of materials used for regeneration [1][2][3]. While some bone substitutes undergo almost immediate biodegradation and resorption, others can be detected on the implant site for several years [1,18].…”
Section: British Biomedical Bulletin Issn 2347-5447mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, Yildirium et al [19] evaluated the bone formation following maxillary sinus augmentation using bovine substitute material bio-oss in combination with VB by means of histologic and histomorphometric examination of human biopsies and histomorphometric examination of human biopsies and the analysis showed 14.7 % newly formed bone and 29.1 % of the surface of the bio-oss granulate was in direct contact with newly formed bone. Study by Lundgren et al [20] indicated that bone grafts or bone substitutes may not be needed to achieve augmentation of the maxillary sinus floor.…”
Section: Disscussionmentioning
confidence: 99%
“…For the clinician it would be valuable to assess the bone regeneration after the implantation of different biomaterials. The effect of various grafts including allogenic bone, alloplastic bone substitutes and their combinations [15][16][17][18][19]20,21] have been extensively studied in animal models [22][23][24][25]26] and in vitro experiments [27,28]. There has also been research assessing the augumentation process with the use of clinical, histological and histomorphometrical analysis in humans [29].…”
Section: Introductionmentioning
confidence: 99%